EFEKTIVITAS METODE DEMONSTRASI DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN PADA PENGAJARAN SISTEM KOLOID - Hamda Situmorang; Manihar Situmorang (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2013)
Abstract Implementation of demonstration method in the teaching of chemistry is assigned as the right strategy to improve students’ achievement as it is proved that the method can bring an abstract concept to reality in the class. The study is conducted to vocational high school students in SMKN1 Pargetteng getteng Sengkut Pakfak Barat at accademic year 2013. The teaching has been carried out three cycles on the teaching of chemistry topic of colloid system. In the study, the class is divided into two class, experiment class and control class. The demontration method is used to teach students in experimental class while the teaching in control class is conducted with lecture method. Both are evaluated by using multiple choise tests before and after the teaching procedures, and the ability of students to answer the problems are assigned as students’ achievements. The results showed that demonstration method improved students’ achievement in chemistry. The students in experimental class who are taughed with demonstration method (M=19.08±0.74) have higher achievements compare with control class (M=12.91±2.52), and both are significantly different (tcalculation 22.85 > ttable 1.66). The effectivity of demostration method in experimental class (97%) is found higer compare to conventional method in control class (91%).